Setting Expectations When Prescribing Medication for the Treatment of Patients With Obesity - Angela Fitch, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
The worldwide prevalence of obesity more than doubled between 1990 and 2022 (men, 4.8%-14.0%; women, 8.8%-18.5%), with similar trends observed for obesity-related diseases, including type 2 diabetes mellitus. Despite this increase in prevalence, many individuals with obesity remain untreated. There are several barriers limiting access to effective care, including the stigma and bias associated with obesity and lack of insurance coverage as a standard job benefit. Additionally, unrealistic expectations for rate of weight-loss and the weight-loss process as well as a lack of proper education on the weight-loss journey and treatment options can contribute to the inability to achieve weight-loss goals and a reluctance to try evidence-based approaches. Therefore, there is a need for effective management and education focusing on individualized treatment and setting viable expectations for the treatment of patients with obesity. Health care providers should compassionately discuss with their patients the importance of weight-loss, the long-term clinical benefits, and expectations for the weight-loss journey, including amount and timing of weight-loss, as well as the potential financial implications associated with obesity treatment. Health care providers should also be able to inform patients along the treatment journey, including about potential adverse events and how they can be managed. Importantly, treatments and decisions should be tailored to each patient using shared decision making with a focus on their characteristics, history, and goals. In this study, the expectations and current use of approved antiobesity medications in the United States are reviewed.